PENDEKATAN COGNITIVE BEHAVIORAL THERAPY (CBT): LITERATUR REVIEW UNTUK MENGATASI STRES AKADEMIK PESERTA DIDIK - Suprianto Baen; Eka Wahyuni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The purpose of this research is to find out the causes of academic stress in students and the impact of applying the cognitive behavioral therapy approach to dealing with academic stress. The method used in this study is in the form of a literature review study, articles are searched through the database using Google Scholar is a web search engine run by Google that indexes scientific literature such as journal articles, academic books, conferences, found using the keywords "academic stress","Cognitive Behavior Therapy”, and “CBT to deal with academic stress”, which were published from 2018 to 2023 and were written in English and Indonesian. Based on data synthesis, 30 selected articles were studied and inputted which were prepared by reviewers for analysis. design, along with the results and conclusions of each paper. Qualitative research, and review articles are included to have a broader picture of this subject. The occurrence of academic stress on students is first the condition (Covid-19) then the occurrence of online learning which according to students is difficult to follow because of various problems such as exams, class rankings, homework, expectations, future achievements, and impacts on health such as suffering from illness headaches, difficulty concentrating, feeling excessive anxiety about everything, easily agitated, even consuming alcohol and drugs excessively. Second, student stress is influenced by personal desires that are not in line with the conditions of the learning environment, such as a dense school curriculum. , making decisions, continuing studies, majors, teachers and friends who have a variety of characters, and experience this on average at the high school level and are female, and the effectiveness of cognitive-behavioral therapy in increasing the locus of control of students who experience academic stress can be seen through the statements contained in the homework that the counselee has given in each session.